Free Tissue Transfer in Acute Burns - Oni, Georgette; Saint-Cyr, Michel; Mojallal, Ali (Journal of Reconstructive Microsurgery, 2012)
Major burn injuries can be devastating for the patients and their carers both in terms of morbidity and mortality. Therefore, it is important to optimize the treatment of the injured patient. After initial resuscitation and physiological stabilization, thorough surgical débridement of the burn is necessary. Often resultant defects can be resurfaced with split skin grafting or local flaps. However, in a small percentage of cases free flap surgery is necessary. Free tissue transfer in burns surgery is rare, but is indicated in those patients in which there is loss of a vascularized surface suitable for grafting such as exposed tendon, or bone following surgical débridement, and in extreme cases for limb salvage. This review article discusses the rationale for free flap surgery in terms of types of burn injuries, perioperative considerations, and summarizes the literature in free tissue transfer in acute burns.
Keywords: free flap surgery; acute burns management; trauma